The Amish Christmas matchmaker - Chapman, Vannetta (Chapman, Vannetta. Indiana Amish brides., 2019)
With her wedding business thriving, Annie Kauffmann could never leave her beloved Amish community. So when handsome Amish cowboy Levi Lapp tries to convince her father to move the family to Texas, she must put a stop to it. If Annie finds Levi a wife, he might forget his dream of moving<U+2026>but can she keep from falling for him herself?